Teach yourself visually Office 2010 - Shoup, Kate , 1972- (Read less-learn more, 2010)
"Are you a visual learner? Do you prefer instructions that show you how to do something--and skip the long-winded explanations? If so, then this book is for you. Open it up and you?ll find clear, step-by-step screen shots that show you how to tackle more than 220 Office 2010 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Office 2010 in no time"--Cover, p. 4